Mind mapping to enhance critical thinking skills in respiratory therapy education - Faisal A. Turkestani; Genevieve P. Zipp; Ziyad Al Nufaiei; Raid Al Zhranei; Fahad Alhadian; Jameel Hakeem; Taha Ismaeil; Saleh S. Algarni; Ayedh D. Al-Ahmari; Mazen Homoud (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The objective of this study was to investigate the use of mind maps as an active teaching strategy to enhance critical thinking skills (CTSs) among respiratory therapy (RT) students in Saudi Arabia. MATERIALS AND METHODS: A total of 86 participants from two RT programs in Saudi Arabian Universities, King Saud bin Abdulaziz University for Health Sciences and The Batterjie Medical College, were randomly assigned to either the mind map group (MMG) or the standard note-taking group (SNTG). With the quasi-experimental design and quantitative method, mean comparisons were made between the groups using an independent t-test. RESULTS: There was no significant change between the pre-SNTG and post-SNTG as measured by the health sciences reasoning test (HSRT) after 15 weeks of standard note-taking (SNT). However, it showed the difference between the pre-MMG and post-MMG (P = .02) as measured by the HSRT after 15 weeks of intervention. There was also a significant change between the post-MMG and SNTG (P = .04) as measured by the HSRT, where the MMG had higher scores. However, the study had limitations, which conceded to the failure of participants in the test and the subjectivity of respondents where they were excluded from the study; also, for generalizability of the result, the study should have been taken beyond Riyadh and Jeddah. CONCLUSION: Prior to this study, the effectiveness of mind mapping (MM) in the respiratory discipline has not yet been explored. It found that mind mapping was effective at improving CTS, while SNT was not, as measured by pre- and post-test HSRT scores. This was the first investigation into MM's impact on CTS within respiratory therapy education.